Evaluasi Rapor Pendidikan Di SMP Progressive Bumi Shalawat - Suherman Suherman; Mufarrihul Hazin; Kaniati Amalia; Amrozi Khamidi; Mochamad Nursalim (Journal on Education, 2025)
The purpose of this study is to evaluate the education report card at Progressive Bumi Shalawat Junior High School, emphasizing the importance of education in encouraging the nation's intellectual growth. Through the implementation of the National Assessment, this school obtained report cards that reflect performance in various aspects, including literacy ability, numeracy, character, and safety conditions, diversity and quality of learning. The results of the evaluation showed that the students' literacy ability was above the minimum competency, with the majority of students reaching the advanced level. However, challenges remain, especially in the psychological well-being of students and the application of diversity principles, which require further attention. This study uses a qualitative-descriptive approach, analyzes data from interviews and documents, and provides recommendations for continuous improvement in the education system in schools. Thus, SMP Progressive Bumi Shalawat is committed to improving the quality of education and providing a better learning experience for all students.